Induction of Rhizoctonia resistance to odontoglossum ringspot virus (ORSV) infection on orchid leaf organ viability - Eka Nuraini Tohari; Mahfut Mahfut; Tundjung Tripeni Handayani; Sri Wahyuningsih (Universitas Lampung, 2021)
Orchid plants are in great demand by the public as ornamental plants that have economic value and the beauty of attractive flower shapes and colors, especially Phalaenopsis and Dendrobium. Related to this, conservation efforts are needed through cultivation. However, these efforts are often hampered by viral infections. One of the viruses that trigger inhibition of orchid cultivation that often appears is ORSV. Control efforts that are relatively safe and efficient can utilize mycorrhizae in orchids which play a role in increasing the absorption of plant nutrients. The use of Phalaenopsis and Dendrobium with the induction of Rhizoctonia sp. against ORSV is a very important alternative biofertilizer and biocontrol agent. The objectives of this study were 1) to determine the effectiveness of orchids induced by Rhizoctonia resistance, 2) to determine the viability of orchid leaf organs to ORSV infection, 3) to determine the viability of orchid root organs resulting from Rhizoctonia resistance to ORSV infection. This study was conducted in January 2021 – March 2021 at the Botanical 2 Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung. This study employed a completely randomized factorial with 6 treatments and 4 replications. The variable observed in this study was the effectiveness of mycorrhizae, leaf and root length, number of leaves and roots, and leaf width. The data obtained were homogenized using Levene's test and then analyzed by ANOVA and Tukey's further test at the 5% level. The results showed that the effectiveness of mycorrhizae occurred on the 3rd day of incubation. In leaf organs, Phalaenopsis amabilis showed an increased response and Dendrobium discolour showed a decreased response in leaf length, width, and number. Meanwhile, in the root organ, Dendrobium discolour showed an increased response and Phalaenopsis amabilis showed a decreased response in root length and number of roots.